Need for accelerating tobacco control in India: findings from the national cancer registry programme. Issue 2 (12th September 2022) - Nath, Anita; SathishKumar, Krishnan; Das, Priyanka; Lakshminarayana, Sudarshan Kondalli; Santhappan, Stephen; Natarajan, Sathya; Karuppasamy, Saravanaraj; Narasimhan, Sandeep; Venkataiah, Ramesha; Mathur, Prashant
Abstract : Objective: To describe the epidemiology of cancer in sites associated with tobacco use in India, according to recent findings from the National Cancer Registry Programme. Methods: The data on cancers in sites associated with tobacco use has been sourced from 28 population-based and 58 hospital-based cancer registries of the National Cancer Registry Programme in India. The data covering a period of 5 years (2012–2016) was taken up for analysis. Results: The highest age-adjusted incidence rate (AAR) among males was reported in the Aizawl district in Mizoram (197.3 per 100 000). The AAR was the highest (121.1 per 100 000) in the Papumpare district in females. The top five leading sites were cancers of the lung (10.7%), mouth (8.7%), oesophagus (6%), tongue (6%) and stomach (5%) among males and cancer of the cervix (10.3%), lung (4.3%), oesophagus (3.3%), mouth (3.3%) and tongue (2.7%) in females. The highest significant increase in AAR, indicated by the annual percentage change was seen among males in Aurangabad (3.4) and females in Kamrup urban (2.4). Except for lung cancer, most patients with other cancer types among both genders presented to the health facility with a locoregional (spread to nearby lymph nodes) disease spread. It is projected that in 2025, there will be 694367 cases of cancers in the sites associated with tobacco use. Conclusion: Tobacco uses in either form and cancer in sites associated with tobacco use are an important matter of public health concern in India. Cancer registries play a crucial role in identifying populations with high cancer incidence in sites associated with tobacco use, monitoring the trends over time, and evaluating the impact of tobacco control measures.